ICOR Analysis on Inequality in Maluku Development - Jefri Tipka (Tensor: Pure and Applied Mathematics Journal, 2022)
The geographical condition of Maluku Province, which is in the form of an archipelago and the uneven distribution of investment, is one of the causes of the development inequality among regions in Maluku Province. Investment as measured by using ICOR can help to see efficiency in investment activities, so this research aims to see the role of investment in relation to equitable development during the 2011-2020 period in Maluku Province. The Linear Regression Method is used to measure how much influence the investment has on the level of unemployment in Maluku Province. The results show that investment is very influential on reducing inequality and helping equality development in Maluku Province. This finding serves as input for the government that until 2020, development inequality still occurs in Maluku Province.